The Utilization from Glucomannan of Porang Flour (Amorphophallus Muelleri Blume) as a Raw Material for Making an Edible Film - Nurlatifah, Ismi; Amyranti, Mutia (BERKALA SAINSTEK, 2023)
Porang (Amorphophallus Muelleri Blume) is a type of tuber that contains various nutrients, especially glucomannan. Besides as being a source of food, the high content of glucomannan can also be used as an alternative for making edible films, because it contains mannan polymers which have the ability to form fine and crystallized fibers. The purpose of this research is to determine the potential of glucomannan in porang tuber flour as a basis for making edible films. Glucomannan used with various variations (3, 6 and 9 grams). The first stages used were testing porang tuber flour and then made edible film base by carrying out various chemical analyzes based on the Japanesse Industrial Standard method. The results showed that the acquisition of water, ash and protein sequentially was 11.782%, 1.821%, 6.275% which conform to the SNI 7939;2013 standards. The 3 gram variation and 0.087 mm thickness of Glucomann showed the best water resistance value of 20.34%. The biodegradability test showed that the 6 grams variation of glucomannan had the best degradation ability, that is 100% for 12 days.